The Effect of Virtual Laboratory using Ethnoscience Concept “Mangeppi Agara” on Students’ Digital Literacy and Science Literacy - Romi Adiansyah; Astuti Muh. Amin (Postgraduate, University of Mataram, 2026)
In this digital age, digital literacy and science literacy are key to comprehending and applying knowledge efficiently. However, modern science education often overlooks local wisdom and ethnoscience, which are rich in cultural values and traditions. Ethnoscience studies can provide material for creating virtual laboratories to help students increase their digital literacy and science literacy. The purpose of this research is to analyze the effect of virtual laboratories using the